أحكام الشركات القابضة والتابعة في الفقه الإسلامي : دراسة تحليلية نقدية لأحكام الشركات القابضة والتابعة - ديسوميمبا، عبد السلام بن واري (Kulliyat Ma'arif al-Wahy wa al-'Ulum al-Insaniyah, al-Jami'ah al-Islamiyah al-'Alamiyah bi- Maliziya, 2006)
In this study, the researcher tried to investigate and explore the rulings of Holding and subsidiary companies comparing with the companies stated by the books of Islamic jurisprudence and the secular law. The researcher started his study by analyzing the definitions of the companies mentioned by jurisprudence comparing with definitions of holding companies, which means a big company who controlled its subsidiaries in terms of financial and administrative matter. Putting a general principle and comprehensive plan design for strategical graphing towards a big economic project. The researcher also analyzes the elements which supported the flourishing of Holding and subsidiary companies across national and International quoting their historical emergence and their development. Also examined analytically the relationship of the contracts stated by Islamic jurisprudence books and the contracts dealing by Holding companies and explained the main points of agreement and disagreement between them. The researcher also explored the rulings of investment in holding and subsidiary companies, their objectives and conditions which is in accordance from Islamic jurisprudence. He studied also the financial rights which as obligatory to the holding and subsidiary companies to pay; such as Tax, Loan and the manner of paying zakah. He adopted a descriptive as well as historical methodology and arrived at some results as follows: the holding and subsidiary companies are in harmony with companies stated by Islamic jurisprudence in terms of operation, profitsharing and share of loses between them. According to the economist’s theory, it is claimed that the government has a role to play in pushing forward the development of holding companies using it as tool in its foreign policy.